PENGARUH E-SERVICE QUALITY, TERHADAP LOYALITAS PELANGGAN YANG DI MODERASI VARIABEL KEPUASAN PELANGGAN (Studi pada Pelanggan Jasa Transportasi Online Gojek di Kota Malang) - Widanarni Pudjiastuti Widanar; Dwi Danesty Deccasari; Dicky Hermawan Putra (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
In the face of increasingly intense competition, Go-Jek needs to innovate in order to provide better services to its customers and attract new customers. One of the methods used is optimizing service delivery through the internet, known as e-service. E-service Quality is a new version of service quality (ServQual). This study aims to analyze whether customer satisfaction can moderate the relationship between E-service Quality and customer loyalty in the online transportation service industry of Gojek in Malang. The population of this study consists of all Gojek customers in Malang. The research sample was randomly selected using the accidental sampling method, with a total of 100 Gojek customers participating as respondents. Descriptive statistical analysis and path analysis using Partial Least Squares (PLS) were employed to analyze the data. The findings of this study indicate that customer satisfaction does not moderate the influence of E-service Quality on customer loyalty. This implies that there is no significant impact between E-service Quality and customer satisfaction on customer loyalty. Conversely, E-service Quality has a strong direct impact on customer loyalty without the moderation of customer satisfaction.